2012
DOI: 10.1371/journal.pone.0037100
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity in CD73/Ecto-5′-Nucleotidase Deficient Mice Induces Renal Injury

Abstract: Extracellular adenosine formed by 5′-ectonucleotidase (CD73) is involved in tubulo-glomerular feedback in the kidney but is also known to be an important immune modulator. Since CD73−/−mutant mice exhibit a vascular proinflammatory phenotype, we asked whether long term lack of CD73 causes inflammation related kidney pathologies. CD73−/−mice (13 weeks old) showed significantly increased low molecule proteinuria compared to C57BL6 wild type controls (4.8≥0.52 vs. 2.9±0.54 mg/24 h, p<0.03). Total proteinuria incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 37 publications
2
31
1
1
Order By: Relevance
“…CD73-null mice spontaneously develop autoimmune diseases such as glomerulitis and peritubular capillaritis, accompanied by enhanced inflammation (Blume et al, 2012). They are also susceptible to polymicrobial sepsis induced by cecal ligation and puncture, and exhibit increased mortality and systemic inflammation (Hasko et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…CD73-null mice spontaneously develop autoimmune diseases such as glomerulitis and peritubular capillaritis, accompanied by enhanced inflammation (Blume et al, 2012). They are also susceptible to polymicrobial sepsis induced by cecal ligation and puncture, and exhibit increased mortality and systemic inflammation (Hasko et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Podocytes and mesangial cells are two of the major cell lineages in the renal glomerulus (27). To delineate which glomerular cell lineage expressed GATA3, we costained kidneys recovered from Gata3 g/ϩ mice with antibodies recognizing CD73 (a mesangial cell marker [28]), synaptopodin (a podocyte marker [29]), or GATA3-GFP expressed from the Gata3 g targeted allele. These colocalization studies demonstrated that a large proportion of GATA3-GFP-positive cells coexpressed CD73 (Fig.…”
Section: B125-g3mentioning
confidence: 99%
“…86 Recent unpublished pilot studies in our laboratory showed that infusion of ATP (for 1 hour on day 14 of pregnancy) in pregnant rats induced a slight but significant increase in blood pressure until 48 hours after infusion. In addition, CD73 knockout mice, which are likely to have elevated ATP levels, display preeclampsia-like symptoms, such as proteinuria, inflammation, endothelial dysfunction, and glomerular endotheliosis, [87][88][89] whereas CD39 overexpression inhibited the induction of preeclampsia in mice. 90 …”
Section: Atp and Adenosine In Preeclampsiamentioning
confidence: 99%